Population Ageing and Government Health Expenditures in New Zealand, 1951-2051 - John Bryant; Audrey Teasdale; Martin Tobias; Jit Cheung; Mhairi McHugh (New Zealand Government, The Treasury, 2004)
The paper uses a simulation model to assess the effects of population ageing on government health expenditures in New Zealand. Population ageing is defined to include disability trends and "distance to death"; government health expenditures are defined to include both acute and long-term care. The model results suggest that population ageing is associated with a large increase in expenditure share of people aged 65 and over, which rises from about 29% of total government health expenditure in 1951 to 63% in 2051. Analysis of demographic and health trends over the period 1951 to 2002 suggests, however, that these trends account for only a small proportion of the total growth in health expenditure. Most expenditure growth is attributable to other factors, such as an expansion in the range of treatments provided, and increases in input prices such as wages. Growth in this non-demographic component of health expenditures has reached 3-4% per year over recent years. Projection results for the period 2002 to 2051 suggest that restraining government expenditure on health to 6-12% of GDP would require long-run growth rates for the non-demographic component of health expenditure that are significantly lower than current rates. In other words, future demographic changes may be less threatening than is often assumed, but it would still not be possible to maintain current growth rates for government health expenditure and avoid substantial increases in the ratio between expenditure and GDP.
Keywords: C53; H51; 330; Fiscal projections; Government health expenditure; Health status; New Zealand